Efeito do tratamento com Euterpe Oleracea (Açaí) no processo de reparo do tendão de aquiles em ratos - SILVA, Dlânio Gabriel Figuêredo (Universidade Federal do Pará, 2017)
Achilles tendon is the largest and strongest tendon in the human body, its excessive use induces microtrauma and activation of signaling pathways that lead to an inflammatory response. The ethanolic extract of Euterpe oleracea(açaí) is a natural product extracted from the fruit of the palm tree.Although evidence suggests an anti-inflammatory and antioxidant effect of this product, there is no data in the literature about such effects on tendon lesion. The aim of this study was to investigate the anti-inflammatory and pro-regenerative effects of ethanolic extract of Euterpe oleracea in a rat model of total Achilles tendon rupture. This study was approved by the Animal Research Ethics Committee (CEPAE-UFPA/206-14). The animals were divided into four groups (n = 24): control; vehicle (0.9% saline); E. oleracea extract (125 μg/mL ethanolic extract of Euterpe oleracea) and methylprednisolone (30 mg/ml). After the respective treatments, the tissue was analyzed at 7, 14 or 21 days post-injury (dpi) by immunohistochemistry with hematoxylin/eosin and collagen autofluorescence. Immunofluorescence for COX2 and measurement of nitrite levels by Griess method were performed at 7 dpi. Treatment with E. oleracea extract accelerated tissue organization and orientation of the cells, similarly to the anti-inflammatory steroid methylprednisolone. This natural product led to an early alignment in collagen fibers as well as in the overall matrix structure when compared to the other groups, which was observed at 7 dpi and maintained at both 14 and 21 dpi. Treatment with E. oleracea extract or methylprednisolone reduced COX2 labeling in comparison to the vehicle at 7 dpi. Reduction in nitrite tissue levels was observed at 7 dpi in groups treated with E. oleracea extract (20.80 ± 2.54 μm/ml) and methylprednisolone (19.40 ± 2.31 μm/ml) compared to vehicle group (29.33 ± 3.98 μm/ml). Treatment with E. oleracea extract improved tissue organization and reduced both COX2 labeling and nitrite levels, suggesting anti-inflammatory and antioxidant effects. Our findings highlight E. oleracea extract as a natural product with potential application in Achilles tendon repair.